Microbial Inoculants: Silver Bullet or Microbial Jurassic Park?. Issue 4 (April 2021) - Jack, Chandra N.; Petipas, Renee H.; Cheeke, Tanya E.; Rowland, Jennifer L.; Friesen, Maren L.
Abstract : The appeal of using microbial inoculants to mediate plant traits and productivity in managed ecosystems has increased over the past decade, because microbes represent an alternative to fertilizers, pesticides, and direct genetic modification of plants. Using microbes bypasses many societal and environmental concerns because microbial products are considered a more sustainable and benign technology. In our desire to harness the power of plant–microbial symbioses, are we ignoring the possibility of precipitating microbial invasions, potentially setting ourselves up for a microbial Jurassic Park? Here, we outline potential negative consequences of microbial invasions and describe a set of practices (Testing, Regulation, Engineering, and Eradication, TREE) based on the four stages of invasion to prevent microbial inoculants from becoming invasive. We aim to stimulate discussion about best practices to proactively prevent microbial invasions. Highlights: Positive results from using microbes in restoration and agricultural research coupled with changing technology have led to increased interest in scaling up and commercializing microbial inoculants as biostimulants and bioprotectants. Ecological research has not kept pace with agricultural and microbiome research with regards to the effect that these introduced microbes have on resident plant and soil communities, and the resulting ecosystem services. Are we unleashing, or have we already unleashed, a tool meant for the betterment of society that we cannot control and may wreak havoc ecologically? Here, we discuss potential consequences of human-assisted microbial invasions. We review current regulatory structures in the USA and provide a general set of practices to decrease the probability of microbial inoculants escaping their intended use and becoming invasive